Intellectual Capital Reporting and Stock Performance in Malaysia - Balaraman, Rajeswary (2007)
Recently, many companies have shown interest in reporting intellectual capital to establish an understanding and to provide disclosure of the central growth factors of the company. This is to achieve a more effective management as well as to increase the company's value. The first objective of this study is to examine the extent of voluntary intellectual capital reporting among the Malaysian companies and how such reporting may be associated with certain organisational attributes, such as industry sector, size and profitability. The second objective is to analyse whether the extent of voluntary intellectual capital reporting has any impact on the stock performance of the companies, in respect of market-to-book ratio and abnormal return upon issuance of annual report